The Role of Rehabilitation Medicine in the Psychological Etiology of Blindness or Visual Impairment: A Critical Synthesis - Clairissa G. Richardson (Disease and Health Research: New Insights Vol. 6, 2024)
Background: Most research and subsequent treatment interventions operate dichotomously in the conceptualization of causality regarding mental health among people with BVI, advancing the conclusion that such problems are either related to physical impairment or social structure. Roughly 3 million adult Americans have a visual impairment or blindness, and over 4 million adults aged 40 and older. Despite data demonstrating an elevated prevalence of mental health symptoms in people with BVI, this population remains largely untreated. The relatively low rates of mental health care service initiation are particularly concerning because individuals with BVI frequently interact with many systems of rehabilitative treatment intended to enhance quality of life. Aim: The present study highlights the Role of Rehabilitation Medicine in the Psychological Etiology of Blindness or Visual Impairment. Patients and Methods: A comprehensive literature review was conducted. The literature review utilized a critical systems typology, whereby relevant literature was selected, reviewed, and analyzed intra and extra-organizationally. In addition, a thorough discussion of disability-related factors was provided, lending a socio-political lens to the problem. Results: Considerable data indicates that short-term mental health care services for people with BVI are ineffective treatment methods, albeit primarily employed in health-rehabilitative processes. Multiple studies offered data indicating the presence of diverse and entangled mental health issues relative to vocational rehabilitation services, mobility tool utility, and emotional reactions to vision loss. Many studies suggested that disability identity work be integrated into health-rehabilitative processes for people with BVI. A critical forum or podcast can provide a means of educative introspection that aids people with BVI to recognize the power that is given, not necessarily power held. Reality therapy, then, can be an organized effort to incorporate into clinical settings which people with BVI are cognizant of, and may specifically request, during assessment or evaluative procedures. Conclusion: To improve the utility of mental health care services for people with BVI, a reenergization of the mental health care needs of this population must occur. Future mental health policy and practice for individuals with BVI can be improved with the help of a podcast or forum that critically examines and educates listeners about the health-rehabilitation issues that impact the provision of mental health care services. In order to improve understanding of this demographic and their particular mental health needs, disability researchers must expedite qualitative, community-based techniques and develop research on integrating critical perspectives in treatment with persons with BVI.